DIGIEDU: Learning Project with Digital Based to Overcome Learning Lost Post Covid-19 Pandemic in Social Science Education Department - Rosmiati Rosmiati; Ahmad Nasori; Nurmala Sari; Iwan Putra; Novia Sri Dwijayanti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The existence of the COVID-19 pandemic adds to the row of problems that exist in tertiary institutions, meaning that we cannot allow this problem to continue because it will hamper the improvement in the quality of graduate learning and the quality of the students it produces. The aim of the research is to improve the quality of learning through digital-based learning projects (DIGIEDU) to address lost learning after the pandemic to increase understanding and absorption of learning. This research is a type of Addie's (1996) development model using the Lee & Owens (2004) model through the use of digital technology development model syntax. The study of product effectiveness in measuring learning is based on assessments from the material validator, media from alpha testing, as well as comments from users and expectations from DIGIEDU product development. Based on the data table, the feasibility and effectiveness scores were obtained from various experts and students. In the media expert's assessment, a score of 82.3% was in the proper category. Assessment from design experts gets a score of 86% in the proper category. In the assessment of the practitioner category, a score of 91.1 was obtained and 82.2 students were in the sufficient category.